Novel Keap1-Nrf2 Protein-Protein Interaction Inhibitor UBE-1099 Ameliorates Progressive Phenotype in Alport Syndrome Mouse Model. Issue 4 (28th April 2022) - Kaseda, Shota; Sannomiya, Yuya; Horizono, Jun; Kuwazuru, Jun; Suico, Mary Ann; Ogi, Sayaka; Sasaki, Ryoko; Sunamoto, Hidetoshi; Fukiya, Hirohiko; Nishiyama, Hayato; Kamura, Misato; Niinou, Saki; et al.
Key Points: UBE-1099 inhibits Keap1-Nrf2 protein-protein interaction and induces Nrf2 activation. UBE-1099 ameliorates the progressive phenotype of an Alport syndrome mouse model. Keap1-Nrf2 protein-protein interaction inhibitor could be a therapeutic drug for glomerulosclerosis and chronic kidney disease. Visual Abstract: Abstract : Background: Bardoxolone methyl activates nuclear factor erythroid 2–related factor 2 (Nrf2) via covalent binding and irreversible inhibition of Kelch-like ECH-associated protein 1 (Keap1), the negative regulator of Nrf2. Ongoing clinical trials of bardoxolone methyl show promising effects for patients with CKD. However, the direct inhibition of Keap1-Nrf2 protein-protein interaction (PPI) as an approach to activate Nrf2 is less explored. Methods: We developed a noncovalent Nrf2 activator UBE-1099, which highly selectively inhibits Keap1-Nrf2 PPI, and evaluated its efficacy on the progressive phenotype in an Alport syndrome mouse model ( Col4a5 -G5X). Results: Similar to bardoxolone methyl, UBE-1099 transiently increased proteinuria and reduced plasma creatinine in Alport mice. Importantly, UBE-1099 improved the glomerulosclerosis, renal inflammation, and fibrosis, and prolonged the life span of Alport mice. UBE-1099 ameliorated the dysfunction of Nrf2 signaling in the renal tissue of Alport mice. Moreover, transcriptome analysis in the glomerulus showed that UBE-1099 induced the expression of genes associated with the cell cycle and cytoskeleton, which may explain its unique mechanism of improvement such as glomerular morphologic change. Conclusions: UBE-1099 significantly ameliorates the progressive phenotype in Alport mice. Our results revealed the efficacy of Keap1-Nrf2 PPI inhibitor for glomerulosclerosis and present a potential therapeutic drug for CKD.